Efficacy and Safety of Oral Pleconaril for Treatment of Colds Due to Picornaviruses in Adults: Results of 2 Double-Blind, Randomized, Placebo-Controlled Trials - Hayden, Frederick G. (Clin Infect Dis, 2003)
The novel capsid-binding antiviral pleconaril inhibits in vitro replication of most rhinoviruses and enteroviruses. Oral pleconaril treatment was studied in 2 parallel randomized, double-blind, placebo-controlled trials. Among 1363 picornavirus-infected participants (65%) in the studies combined, the median time to alleviation of illness was 1 day shorter for pleconaril recipients than for placebo recipients (P > .001). Cold symptom scores and frequency of picornavirus cultured from nasal mucus specimens were lower among pleconaril recipients by day 2 of treatment. No treatment effects were seen in those without picornavirus infection. Pleconaril was associated with a higher incidence of nausea (6% vs. 4%) and diarrhea (9% vs. 7%) and with small increases in mean serum cholesterol levels and platelet counts, compared with baseline measurements. A subsequent 6-week prophylaxis study found that pleconaril induces cytochrome P-450 3A enzymes, which metabolize a variety of drugs, including ethinyl estradiol. Early pleconaril treatment was well tolerated and significantly reduced the duration and severity of colds due to picornaviruses in adults.